Preparation method of composite denitration catalyst based on Cu-BTC metal organic framework, composite denitration catalyst and denitration catalytic filter material

Through the preparation method of composite denitrification catalyst based on Cu-BTC metal organic framework, the problem of low catalytic activity of low temperature denitrification in the prior art is solved, and the efficient, stable and low-cost NOx conversion effect is achieved.

CN119455969APending Publication Date: 2025-02-18ANHUI SHIQING ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411436889.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing denitrification catalysts have low catalytic activity in low temperature environments, and are relatively stable and costly.

Method used

A composite denitrification catalyst based on Cu-BTC metal organic frame was prepared by template method, post-modification impregnation and high-temperature carbonization-high-temperature oxidation segmented calcination pyrolysis, and CuO/Cu2O/Mn3O4-x composite denitrification catalyst was prepared.

Benefits of technology

The catalytic activity of the catalyst in low temperature environment is improved, the stability of the material structure is enhanced, the cost is reduced, and efficient NOx conversion and N2 selectivity is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455969A_ABST
    Figure CN119455969A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite denitration catalyst based on a Cu-BTC metal organic framework, the composite denitration catalyst and a denitration catalytic filter material, and relates to the technical field of denitration catalysis. The preparation method comprises the following steps: taking Cu-BTC as a sacrificial template, dipping the sacrificial template in a manganese acetate mixed solution with a certain concentration, carrying out rotary evaporation at a certain temperature to dryness, then putting into a drying oven to dry a sample, and finally preparing the CuO / Cu2O / Mn3O4 composite denitration catalytic material by adopting a high-temperature carbonization and high-temperature oxidation sectional calcination method. The composite denitration catalytic material prepared in the invention presents a spherical morphology with certain pores and uniform distribution, metal oxides with different valence states have excellent oxidation-reduction performance, electron transfer between NH3 and NOx is promoted, and the process of a reduction reaction is accelerated; the metal with different valence states can promote the reaction between NH3 and NOx, and the prepared composite denitration catalyst is stable in structure, low in temperature, efficient, green, environmentally friendly, non-toxic and harmless.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of denitration catalysis, and in particular to a preparation method of a composite denitration catalyst based on a Cu-BTC metal organic framework, a composite denitration catalyst and a denitration catalytic filter material. Background Art

[0002] The rapid development of industry and economy is accompanied by a series of environmental pollution problems. As people's requirements for quality of life improve, they pay more and more attention to environmental pollution problems, among which the emission of nitrogen oxides, chemical smog, acid rain, greenhouse effect and ozone layer damage have attracted much attention. However, the sources of nitrogen oxides are wide, including power plants, kilns (flue gas) in industrial production, motor vehicles, etc.

[0003] Traditional denitrification catalysts V2O5 / TiO2 have excellent denitrification efficiency, which can reach more than 90%, helping to reduce industrial emissions of nitrogen oxides. However, this type of catalyst has a high active temperature, poor stability and high cost. Therefore, research on low-temperature, efficient and stable denitrification catalytic materials is crucial to the conversion of nitrogen oxides.

[0004] At present, the industry generally uses NH3-SCR (selective catalytic reduction) technology to effectively control nitrogen oxide emissions. The key to the catalysis of NH3-SCR technology lies in the different metal elements in the catalyst. Different metal elements have different electronic structures and chemical properties. They can show different catalytic activities, redox capabilities and ultimately achieve catalytic efficiencies during the catalytic reaction. The structures generated by different metal elements are also different. The stability of catalysts with different structures varies, which affects the denitrification efficiency. Through research, it was found that introducing a second metal element into a single metal catalyst can enhance electron transfer and improve the activity of the catalyst. It can also enhance the stability of the material structure and improve the denitrification catalytic efficiency.

[0005] At present, metal-organic framework materials are widely used in the field of denitrification catalysis due to their excellent specific surface area, high porosity and controllable crystal size, which helps to improve the denitrification catalytic efficiency. For example, metal-organic framework materials such as M-MOF-74 (M=Mn, Co, Ni, Fe), Cu-BTC, MIL-100 (Fe) have outstanding performance in this regard; however, their denitrification catalytic activity is low under low temperature conditions. Summary of the invention

[0006] In order to solve at least one of the above technical problems, a denitration catalyst with high denitration catalytic activity under low temperature environment is developed. The present application provides a preparation method of a composite denitration catalyst based on Cu-BTC metal organic framework, a composite denitration catalyst and a denitration catalytic filter material.

[0007] On the one hand, the present application provides a method for preparing a composite denitration catalyst based on a Cu-BTC metal organic framework, comprising the following steps:

[0008] S1. Dissolve Cu(NO3)2·3H2O in deionized water to obtain solution A, and dissolve trimesic acid in a mixed solution of DMF and ethanol to obtain solution B;

[0009] S2, pouring solution A into solution B, stirring and mixing, and pouring into a reactor for reaction; cooling to room temperature after the reaction, and obtaining Cu-BTC powder by centrifugal separation, washing, soaking, and drying;

[0010] S3, dissolving anhydrous manganese acetate powder in a mixed solution of deionized water and anhydrous ethanol, and adding the Cu-BTC powder prepared in S2, stirring and mixing evenly; after standing for reaction, heating and evaporating to dryness, and constant temperature drying to obtain an intermediate;

[0011] S4. The intermediate prepared in S3 is placed in a nitrogen atmosphere, heated and calcined, then switched to an oxygen atmosphere for calcination, and cooled to room temperature to obtain a composite denitration catalyst.

[0012] Optionally, in the solution A, the addition ratio of Cu(NO3)2·3H2O to deionized water is 1.4142 g:30 ml;

[0013] In the B solution, the addition ratio of trimesic acid, DMF and ethanol is 1.2142 g:15 ml:15 ml;

[0014] The weight ratio of Cu(NO3)2·3H2O in the A solution to trimesic acid in the B solution is 1.4142:1.2142.

[0015] Optionally, in S3, anhydrous manganese acetate powder is dissolved in a mixed solution of deionized water and anhydrous ethanol, and the addition ratio of anhydrous manganese acetate powder, deionized water and anhydrous ethanol is 0.875 g to 1.75 g: 15 ml: 15 ml;

[0016] The weight ratio of the anhydrous manganese acetate powder to the Cu-BTC powder is 1:1.

[0017] Optionally, in S2, the reaction temperature of solution A and solution B in the reactor is 120° C., and the reaction time is 12 h.

[0018] Optionally, in S2, the washing treatment is: washing with DMF and anhydrous ethanol for 3 times respectively;

[0019] And / or, the soaking treatment is: soaking in anhydrous ethanol for 24 hours, during which the anhydrous ethanol is replaced every 12 hours;

[0020] And / or, the drying treatment is: drying at 100° C. for 12 hours.

[0021] Optionally, in S3, the stirring speed is 500 rpm and the stirring time is 5 min;

[0022] And / or, the static reaction time is 2h;

[0023] And / or, the heating evaporation to dryness treatment is: the temperature is raised to 90° C. and rotary evaporation to dryness;

[0024] And / or, constant temperature drying treatment: constant temperature drying treatment at 100° C. for 12 hours.

[0025] Optionally, in S4, under a nitrogen atmosphere, the temperature is raised to 300° C. at a heating rate of 5° C. / min, calcined and kept warm for 1 hour; then, the temperature is switched to an oxygen atmosphere under a constant temperature state and calcined for 1 hour, and then cooled to room temperature to obtain a composite denitration catalyst.

[0026] In the second aspect, the present application provides a composite denitration catalyst prepared by the above preparation method; the composite denitration catalyst is spherical, with a diameter of 8 to 10 μm, and the surface is covered with flaky micro-nano structures; the chemical formula of the composite denitration catalyst is: CuO / Cu2O / Mn3O 4-x (x=1 or 2).

[0027] In a third aspect, the present application provides a denitration catalytic filter material, comprising the above-mentioned composite denitration catalyst.

[0028] In summary, the present application includes at least one of the following beneficial technical effects:

[0029] 1. The catalyst of the present application is prepared by template method, post-modification impregnation and high-temperature carbonization-high-temperature oxidation staged calcination pyrolysis. The prepared catalyst has excellent specific surface area, mesoporous structure, large pore size, and the same metal with different chemical valence states is conducive to the transfer of electrons, thereby promoting NO x The electron transfer between NH3 and NH3 accelerates the reduction reaction;

[0030] 2. The synergistic effect of the two metals makes the Cu dispersed evenly on the surface of the catalyst, adding more acidic active sites, improving the catalytic activity, and ultimately increasing the NO x Conversion rate and N2 selectivity; 3. The catalyst has a stable structure, is efficient at low temperature, is green and environmentally friendly, and is non-toxic and harmless. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the XRD pattern of Cu-BTC prepared in the examples of this application;

[0032] Figure 2 This is a SEM image of Cu-BTC prepared in the examples of this application;

[0033] Figure 3 The XRD diagram of the composite denitration catalyst prepared in the example of the present application;

[0034] Figure 4 This is a SEM image of the composite denitration catalyst prepared in the examples of this application;

[0035] Figure 5 This is a nitrogen adsorption and desorption data diagram of the composite denitration catalyst prepared in the example of the present application;

[0036] Figure 6 This is a pore size distribution diagram of the composite denitration catalyst prepared in the examples of this application;

[0037] Figure 7 This is a catalytic performance diagram of the composite denitration catalyst prepared in the examples of this application. DETAILED DESCRIPTION

[0038] The present application designs a method for preparing a composite denitration catalyst based on a Cu-BTC metal organic framework, comprising the following steps:

[0039] S1. Dissolve Cu(NO3)2·3H2O in deionized water to obtain solution A, and dissolve trimesic acid in a mixed solution of DMF and ethanol to obtain solution B;

[0040] S2, pouring solution A into solution B, stirring and mixing, and pouring into a reactor for reaction; cooling to room temperature after the reaction, and obtaining Cu-BTC powder by centrifugal separation, washing, soaking, and drying;

[0041] S3, dissolving anhydrous manganese acetate powder in a mixed solution of deionized water and anhydrous ethanol, and adding the Cu-BTC powder prepared in S2, stirring and mixing evenly; after standing for reaction, heating and evaporating to dryness, and constant temperature drying to obtain an intermediate;

[0042] S4. The intermediate prepared in S3 is placed in a nitrogen atmosphere, heated and calcined, then switched to an oxygen atmosphere for calcination, and cooled to room temperature to obtain a composite denitration catalyst.

[0043] The present application adopts the above preparation method to prepare a composite denitration catalyst, which is spherical, with a diameter of 8 to 10 μm and a surface covered with a flaky micro-nanostructure; the chemical formula of the composite denitration catalyst is: CuO / Cu2O / Mn3O 4-x (x=1 or 2).

[0044] The present application also prepares a denitration catalytic filter material through the above-mentioned composite denitration catalyst.

[0045] The present invention aims to provide a method of using Cu-BTC as a sacrificial template, impregnating a mixed solution of manganese acetate of a certain concentration, rotating and drying at a certain temperature, and then placing the sample in an oven to dry it. Finally, a high-temperature carbonization and high-temperature oxidation segmented calcination method is used to prepare a CuO / Cu2O / Mn3O4 composite denitration catalytic material. This segmented calcination method can maintain the carbon skeleton structure of Cu-BTC to a certain extent and can fully utilize the porous skeleton characteristics of MOF. In the subsequent high-temperature oxidation process, the pore structure, specific surface area, crystal structure, morphology and size of the metal oxide are regulated to optimize the performance of the catalytic material. The research results show that the CuO / Cu2O / Mn3O4 composite denitration catalytic material prepared by pyrolysis of metal organic framework materials presents a spherical morphology with certain pores and uniform distribution. Metal oxides of different valence states have excellent redox properties, and the transfer of their electrons promotes the conversion of NH3 and NO x The electron transfer between them accelerates the reduction reaction; at the same time, metals with different valence states can serve as the center of the selective catalytic reduction of NH3, promoting the x In addition, the presence of metals with different valence states also affects the acidity of the catalyst surface. Adding more metal Lewis acid sites is more conducive to attracting adsorbed NH3 to be activated into reactive -NH2 on the Lewis acid sites, and then reacting with NO x A reaction occurs, promoting the reaction; finally, the bimetallic synergistic effect of Cu and Mn makes Cu more evenly distributed on the catalyst surface, producing more acidic sites and making the catalytic reaction on the material surface faster.

[0046] The metal organic framework used in the preparation process of the composite denitration catalyst is exemplified by Cu-BTC; the copper salt is exemplified by Cu(NO3)2·3H2O; the prepared CuO / Cu2O / Mn3O 4-x The catalyst is used to prepare a composite denitration filter material, which can be used for ammonia selective catalytic reduction (NH3-SCR).

[0047] The present application is further described in detail below with reference to the accompanying drawings and embodiments.

[0048] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products. Specific embodiments

[0050] Example 1

[0051] 1.4142 g of Cu(NO3)2·3H2O was dissolved in 30 ml of deionized water, which was recorded as solution A. 1.2142 g of trimesic acid was dissolved in a mixed solution of 15 ml of DMF and 15 ml of ethanol, which was recorded as solution B.

[0052] Then, solution A was slowly poured into solution B and stirred on a magnetic stirrer for 5 minutes to make the mixture uniform. Then, the mixed solution was poured into a 100 ml polytetrafluoroethylene reactor and reacted at 120° C. for 12 hours.

[0053] After the reaction is completed, cool to room temperature, separate the product with a centrifuge, obtain a blue sample, and wash it with DMF and anhydrous ethanol three times. The final sample needs to be soaked in anhydrous ethanol for 24 hours, and the anhydrous ethanol is replaced every 12 hours. Finally, the obtained sample is placed in an oven and dried at 100°C for 12 hours to obtain Cu-BTC blue powder.

[0054] Weigh 1.75g ​​of anhydrous manganese acetate white powder and dissolve it in 30ml mixed solution (15ml deionized water + 15ml anhydrous ethanol), then slowly add 1.75g ​​Cu-BTC to the above solution and stir it on a magnetic stirrer at 500rpm for 5min to mix it evenly. Then place the mixed solution at room temperature for 2h to promote the initial interaction and binding between molecules. Then, raise the temperature to 90℃ and evaporate it to dryness. After completing the above steps, carefully transfer the sample to an oven and dry it at a constant temperature of 100℃ for 12h. The obtained sample is recorded as an intermediate.

[0055] The intermediate was placed in a tubular furnace, heated to 300 °C at a heating rate of 5 °C / min in a nitrogen atmosphere, and calcined for 1 h, then switched to an oxygen atmosphere and continued to calcine for 1 h, and finally naturally cooled to room temperature to obtain a composite denitration catalyst, recorded as CuO / Cu2O / Mn3O 4-1 .

[0056] Example 2

[0057] 1.4142 g of Cu(NO3)2·3H2O was dissolved in 30 ml of deionized water, which was recorded as solution A. 1.2142 g of trimesic acid was dissolved in a mixed solution of 15 ml of DMF and 15 ml of ethanol, which was recorded as solution B.

[0058] Then, solution A was slowly poured into solution B and stirred on a magnetic stirrer for 5 minutes to make the mixture uniform. Then, the mixed solution was poured into a 100 ml polytetrafluoroethylene reactor and reacted at 120° C. for 12 hours.

[0059] After the reaction is completed, cool to room temperature, separate the product with a centrifuge, obtain a blue sample, and wash it with DMF and anhydrous ethanol three times. The final sample needs to be soaked in anhydrous ethanol for 24 hours, and the anhydrous ethanol is replaced every 12 hours. Finally, the obtained sample is placed in an oven and dried at 100°C for 12 hours to obtain Cu-BTC blue powder.

[0060] Weigh 0.875g of anhydrous manganese acetate white powder and dissolve it in 30ml mixed solution (15ml deionized water + 15ml anhydrous ethanol), then slowly add 1.75g ​​Cu-BTC to the above solution and stir it on a magnetic stirrer at 500rpm for 5min to mix it evenly. Then place the mixed solution at room temperature for 2h to promote the initial interaction and binding between molecules. Then, raise the temperature to 90℃ and evaporate it to dryness. After completing the above steps, carefully transfer the sample to an oven and dry it at a constant temperature of 100℃ for 12h. The obtained sample is recorded as an intermediate.

[0061] The intermediate was placed in a tubular furnace, heated to 300 °C at a heating rate of 5 °C / min in a nitrogen atmosphere, and calcined for 1 h, then switched to an oxygen atmosphere and continued to calcine for 1 h, and finally naturally cooled to room temperature to obtain a composite denitration catalyst, recorded as CuO / Cu2O / Mn3O 4-2 .

[0062] The specific surface area, average pore diameter and total pore volume of the composite denitration catalyst prepared in Examples 1 to 2 are shown in Table 1.

[0063] Table 1

[0064]

[0065] The denitration performance of the composite denitration catalyst prepared in the above Examples 1 to 2 was tested as follows.

[0066] 0.1g of the composite denitration catalyst prepared in Examples 1 to 2 above was filled into a pyrolysis quartz tube filled with quartz wool, and then some quartz wool was placed above the catalyst to prevent the escape of granular powder. 500ppm NO, 500ppm NH3, 3vol% O2, and Ar were introduced into the pyrolysis quartz tube as the balance gas. The total gas flow rate was 500ml / min. The gas was ventilated for 45min to eliminate air interference, and then the test was started with a temperature interval of 25°C. When the actual temperature of each temperature interval was reached, it stayed for 5 minutes, and the catalytic data of various gases on the gas analyzer were recorded. The test temperature range was 100 to 300°C. The experiment was tested at least three times under each reaction condition. The NO was determined using a Wanandi POT400 gas analyzer. x Content. xThe conversion and N2 selectivity were calculated using the following formula.

[0067]

[0068] Test results such as Figure 7 As shown. Figure 7 It can be seen from the data that the catalytic effect of the composite denitration catalyst prepared in the present application is efficient and stable, and the NO conversion rate is significantly improved with the increase of temperature.

[0069] pass Figure 7 It can be seen that among the two catalysts prepared in the above examples, the CuO / Cu2O / Mn3O prepared in Example 1 4-1 The catalytic effect of the CuO / Cu2O / Mn3O prepared in Example 2 is significantly better than that of the CuO / Cu2O / Mn3O prepared in Example 2 in the temperature range of 50-250°C. 4-2 Example 1 Preparation of CuO / Cu2O / Mn3O 4-1 The composite denitrification catalyst has better catalytic performance in low-temperature denitrification catalysis.

[0070] In summary, the composite denitrification catalyst prepared in this application can be used for low-temperature denitrification catalysis to improve NO x The conversion rate and selectivity of N2 are high, and the process conditions used are mild, which will not cause corrosion to the equipment, and has high catalytic performance. The catalyst is green and environmentally friendly, high-efficiency and stable at low temperature, and low in price. It is an ideal low-temperature denitrification catalyst material, which can significantly improve NO x The conversion rate and N2 selectivity of CuO / Cu2O / Mn3O prepared in Example 1 are 4-1 The catalytic performance of the composite denitrification catalyst is better at low temperatures.

[0071] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a composite denitration catalyst based on a Cu-BTC metal organic framework, characterized in that: The following steps are involved: S1. Dissolve Cu(NO3)2·3H2O in deionized water to obtain solution A, and dissolve trimesic acid in a mixed solution of DMF and ethanol to obtain solution B; S2, pouring solution A into solution B, stirring and mixing, and pouring into a reactor for reaction; cooling to room temperature after the reaction, and obtaining Cu-BTC powder by centrifugal separation, washing, soaking, and drying; S3, dissolving anhydrous manganese acetate powder in a mixed solution of deionized water and anhydrous ethanol, and adding the Cu-BTC powder prepared in S2, stirring and mixing evenly; after standing for reaction, heating and evaporating to dryness, and constant temperature drying to obtain an intermediate; S4. The intermediate prepared in S3 is placed in a nitrogen atmosphere, heated and calcined, then switched to an oxygen atmosphere for calcination, and cooled to room temperature to obtain a composite denitration catalyst.

2. The preparation method according to claim 1, characterized in that: In the solution A, the addition ratio of Cu(NO3)2·3H2O to deionized water is 1.4142 g:30 ml; In the B solution, the addition ratio of trimesic acid, DMF and ethanol is 1.2142 g:15 ml:15 ml; The weight ratio of Cu(NO3)2·3H2O in the A solution to trimesic acid in the B solution is 1.4142:1.2142.

3. The preparation method according to claim 1, characterized in that: In S3, anhydrous manganese acetate powder is dissolved in a mixed solution of deionized water and anhydrous ethanol, and the addition ratio of anhydrous manganese acetate powder, deionized water and anhydrous ethanol is 0.875g-1.75g:15ml:15ml; The weight ratio of the anhydrous manganese acetate powder to the Cu-BTC powder is 1:

1.

4. The preparation method according to claim 1, characterized in that: In S2, the reaction temperature of solution A and solution B in the reactor is 120° C., and the reaction time is 12 h.

5. The preparation method according to claim 1, characterized in that: In S2, the washing treatment is: washing with DMF and anhydrous ethanol for 3 times respectively; And / or, the soaking treatment is: soaking in anhydrous ethanol for 24 hours, during which the anhydrous ethanol is replaced every 12 hours; And / or, the drying treatment is: drying at 100° C. for 12 hours.

6. The preparation method according to claim 1, characterized in that: In S3, the stirring speed is 500 rpm and the stirring time is 5 min; And / or, the static reaction time is 2h; And / or, the heating evaporation to dryness treatment is: the temperature is raised to 90° C. and rotary evaporation to dryness; And / or, constant temperature drying treatment: constant temperature drying treatment at 100° C. for 12 hours.

7. The preparation method according to claim 1, characterized in that: In S4, the temperature is raised to 300° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, and calcined and kept at this temperature for 1 hour; then, the temperature is switched to an oxygen atmosphere under a constant temperature state, and the calcination is continued for 1 hour, and then the composite denitration catalyst is obtained by cooling to room temperature.

8. A composite denitration catalyst, characterized in that: Prepared by the preparation method described in claim 1; the composite denitration catalyst is spherical, with a diameter of 8 to 10 μm, and the surface is covered with flaky micro-nano structures; the chemical formula of the composite denitration catalyst is: CuO / Cu2O / Mn3O 4-x (x=1 or 2).

9. A denitration catalytic filter material, characterized in that: It includes the composite denitration catalyst as described in claim 8.

Citation Information

Cited By

  • Honeycomb spherical manganese-copper bimetallic oxide denitration catalyst and preparation method and equipment thereof

    CN120532512A